The variety of values essays on morality, meaning, and love - Wolf, Susan R. 1952- (Oxford University Press, 2014)
For more than thirty years, the leading moral philosopher Susan Wolf has written about moral and non-moral values and the relation between them. This volume collects Wolf's most important essays on the topics of morality, love, and meaning, ranging from her classic essay 'Moral Saints' to her most recent 'The Importance of Love'
Keywords: Values; Ethics